Numerical study of laminar natural convection of Cu-water nanofluid in concentric annuli with four radial fins. (1st January 2012) - Sheikhzadeh, G.A.; Arbaban, M.
Laminar natural convection of Cu-water nanofluid between two horizontal concentric cylinders with four radial fins attached to the inner cylinder is studied numerically. The inner and outer cylinders are maintained at constant temperature Ti and To, respectively, with Ti > To . The governing equations in the polar two-dimensional space with the respective boundary conditions are solved by using the finite volume method. The hybrid-scheme is used to discretise the convection terms. In order to couple the velocity field and the pressure in the momentum equations, the well-known SIMPLER-algorithm is adopted. Using the developed code, a parametric study is undertaken, and the effects of the Rayleigh number, the fins length, and the volume fraction of the nanoparticles on the fluid flow and heat transfer inside the annuli are investigated. In this study, the fins length ranges from 0.1 to 0.4, the Rayleigh number ranges from 10 3 to 10 5, and volume fraction of nanoparticles ranges from 0 to 0.1. It is observed from the results by increasing fins length, the average Nusselt number decreases but heat transfer rate increases. Also the average Nusselt number increases with increasing both the Rayleigh number and the volume fraction of the nanoparticles.